2020
DOI: 10.18510/hssr.2020.818
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Attitudes and Factors Influencing Organ Donation Decisions Among University Students in Pakistan: A Qualitative Study

Abstract: Purpose: The main purpose of this study was to identify factors that were important in posthumous organ donation decisions in a developing country such as Pakistan. Methodology: A qualitative study was conducted with 50 semi-structured interviews among students of one public and one private university in Lahore (Pakistan) to understand their attitudes and factors influencing their decisions on posthumous organ donations. Purposive sampling technique was used in this study. The interview questions focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This suggests that decisions made in this context not only depend on the respondents, but other important influences could also be the target for promoting participants' decisions on kidney donations. 51 The current results revealed that knowledge is another important and significant factor associated with kidney donation intentions. This result is also consistent with a study conducted in Nigeria and Saudi Arabia, which indicated that knowledge had a significant association with the intention to donate a kidney, indicating that having knowledge regarding kidney donation may have a profound importance in removing and/or decreasing the barriers to participants' decisions about kidney donation.…”
mentioning
confidence: 57%
“…This suggests that decisions made in this context not only depend on the respondents, but other important influences could also be the target for promoting participants' decisions on kidney donations. 51 The current results revealed that knowledge is another important and significant factor associated with kidney donation intentions. This result is also consistent with a study conducted in Nigeria and Saudi Arabia, which indicated that knowledge had a significant association with the intention to donate a kidney, indicating that having knowledge regarding kidney donation may have a profound importance in removing and/or decreasing the barriers to participants' decisions about kidney donation.…”
mentioning
confidence: 57%
“…However, they feared family and social impacts. 17 Ali et al evaluated the awareness and impression of clinical undergraduates in Pakistan. There was a huge degree of information from the press and electronic media.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, Veseli et al (2021) discovered that feeling grateful raises non-donors personal moral standards. In a study in Pakistan, Umair et al (2020) found that most of the respondents had a positive thought for post-obit organ donation yet moral norms are very vital in driven the choice-taking procedure for organ donation following past rest.…”
Section: Literature Reviewmentioning
confidence: 99%